2023
DOI: 10.1137/21m1457205
|View full text |Cite
|
Sign up to set email alerts
|

Greedy Causal Discovery Is Geometric

Abstract: The purpose of this paper is twofold. We investigate a simple necessary condition, called the rhombus criterion, for two vertices in a polytope not to form an edge and show that in many examples of 0/1-polytopes it is also sufficient. We explain how also when this is not the case, the criterion can give a good algorithm for determining the edges of high-dimenional polytopes.In particular we study the Chordal graph polytope, which arises in the theory of causality and is an important example of a characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…To do this we interpret i → j in G to mean i being a direct cause of j. Studený, Hemmecke, and Lindner transformed this question into a linear program over CIM n [16,18]. The authors of [9] showed that the edge structure of CIM n is of particular interest. In their paper we are given a geometric interpretation of several greedy algorithms as edge-walks over CIM n and its faces.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To do this we interpret i → j in G to mean i being a direct cause of j. Studený, Hemmecke, and Lindner transformed this question into a linear program over CIM n [16,18]. The authors of [9] showed that the edge structure of CIM n is of particular interest. In their paper we are given a geometric interpretation of several greedy algorithms as edge-walks over CIM n and its faces.…”
Section: Introductionmentioning
confidence: 99%
“…In their paper we are given a geometric interpretation of several greedy algorithms as edge-walks over CIM n and its faces. In particular, for any undirected graph G, the face [9] (of CIM n ) is studied. A complete characterisation of the edges of CIM G when G is a tree or a cycle was recently discovered [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations